2022
DOI: 10.3389/fneur.2021.740338
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Baroreflex and Cerebral Autoregulation in Patients With Cerebral Vasospasm After Aneurysmal Subarachnoid Hemorrhage

Abstract: Introduction: Common consequences following aneurysmal subarachnoid hemorrhage (aSAH) are cerebral vasospasm (CV), impaired cerebral autoregulation (CA), and disturbance in the autonomic nervous system, as indicated by lower baroreflex sensitivity (BRS). The compensatory interaction between BRS and CA has been shown in healthy volunteers and stable pathological conditions such as carotid atherosclerosis. The aim of this study was to investigate whether the inverse correlation between BRS and CA would be lost i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The impact of BRS on SAH patients’ clinical course has been analyzed in several studies [ 30 33 ]. It was shown that an inverse compensatory correlation between BRS and CA is observed for SAH patients who avoided CV occurrence, whereas this relationship was lost in patients who experienced CV, both before and during vasospasm [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The impact of BRS on SAH patients’ clinical course has been analyzed in several studies [ 30 33 ]. It was shown that an inverse compensatory correlation between BRS and CA is observed for SAH patients who avoided CV occurrence, whereas this relationship was lost in patients who experienced CV, both before and during vasospasm [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The impact of BRS on SAH patients’ clinical course has been analyzed in several studies [ 30 33 ]. It was shown that an inverse compensatory correlation between BRS and CA is observed for SAH patients who avoided CV occurrence, whereas this relationship was lost in patients who experienced CV, both before and during vasospasm [ 30 ]. Decreased BRS within the first five days following SAH was found to be associated with regional cerebral deoxygenation [ 31 ] and consequently with poor outcomes [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation